Kajian Permasalahan Sistem Saliran yang Menyumbang kepada Berlakunya Banjir Kilat - Syahrin, Nurfatin Nadia; Seow, Ta Wee; Mohamed, Sulzakimin (Research in Management of Technology and Business, 2024)
Flash floods that occur every year can threaten the safety of residents and cause property losses to residents. The drainage system in an area plays a role in the occurrence of flash floods. The problem for this study is related to the problem of a drainage system that does not work and is not suitable to the extent that it contributes to the occurrence of flash floods. Objective for this study is to identify the type of drainage system used in flash flood areas, to study the effectiveness of the drainage system built on the local population and the environment as well as to propose suitable strategies to ensure the effectiveness of the drainage system in the study area. This study is focused on the area of Kampung Ismail and Kampung Paya Besar, Negeri Sembilan. Next, this study was done to identify the best strategy that needs to be done to solve the problem of the drainage system that causes flash floods. This study was completed by using a qualitative method, namely interviews related to the drainage system in the study area. A total of five respondents were selected in this study. The parties involved as respondents are representatives of JPS, PBT and also representatives of residents in the study area. The results of this study show that the drainage system used in each area is different according to the needs of the area. The construction of the existing drainage system has a positive effect on the population when the flood statistics in the study area are reduced from 2022 to 2023. The main strategy chosen to solve the problem of the drainage system is through the preservation of water catchment areas as the key to effective water resource management by taking steps- proactive measures. Recommendations to overcome the problem of flash floods are to use a flood warning system and increase cooperation between agencies in effective monitoring in the study area. In conclusion, the researcher hopes that the cooperation of all parties involved in maintaining the drainage system can continue so that flash floods can be reduced, and the sustainability of nature is more guaranteed.